Implementation of Service Oriented Architecture in Mobile Applications to Improve System Flexibility, Interoperability, and Scalability - Afrizal Zein (Journal of Information System, Technology and Engineering, 2024)
This research aims to apply Service Oriented Architecture (SOA) to mobile applications to improve the flexibility, interoperability, and scalability of the system. SOA is an approach that enables better integration between different components in an application architecture. Mobile applications, as an integral part of everyday life, require high flexibility and adaptability to changing user needs. The research method used involves application requirements analysis, SOA architecture design, and implementation on an existing mobile application. Through the implementation of SOA, resource management and service distribution become more efficient, making it easy to add or change features without affecting the entire system. Test results show improved application performance and responsiveness, along with the ability to easily integrate services from multiple sources. In addition, the SOA architecture provides flexibility in the development and maintenance of mobile applications, accelerating the development process and minimizing the impact of changes. This research contributes to the development of mobile applications by introducing the SOA approach as an architectural foundation. The implementation of SOA in mobile applications is expected to guide developers in creating systems that are more resilient, adaptive, and easy to integrate with rapidly evolving software environments.